2020
DOI: 10.3390/en13246718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Oxide Nanoparticles on the Properties of Water-Based Drilling Fluids

Abstract: In recent years, several studies have indicated the impact of nanoparticles (NPs) on various properties (such as viscosity and fluid loss) of conventional drilling fluids. Our previous study with commercial iron oxide NPs indicated the potential of using NPs to improve the properties of a laboratory bentonite-based drilling fluid without barite. In the present work, iron oxide NPs have been synthesized using the co-precipitation method. The effect of these hydrophilic NPs has been evaluated in bentonite and KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Terms Si, Si-C, and Si-N are used for silica, surface modified and NYACOL NPs, respectively thought the text. Synthesis and coating of iron oxide NPs with XG was done based on our previous work [18]. Terms Fe NPs and Fe-XG NPs are used for iron oxide and iron oxide coated with XG throughout the text.…”
Section: Methodsmentioning
confidence: 99%
“…Terms Si, Si-C, and Si-N are used for silica, surface modified and NYACOL NPs, respectively thought the text. Synthesis and coating of iron oxide NPs with XG was done based on our previous work [18]. Terms Fe NPs and Fe-XG NPs are used for iron oxide and iron oxide coated with XG throughout the text.…”
Section: Methodsmentioning
confidence: 99%
“…The point of interception with the shear stress is known as the yield point and it is the minimum stress required to initiate flow. Yield point should be more than zero [9]. The Bingham plastic model equation is given by:…”
Section: Bingham Plastic Modelmentioning
confidence: 99%
“…According to William, Jay Karen Maria, et al (2014),adding small quantities of zinc oxide and copper oxide nano particles to the drilling mud enhanced the viscosity, thermal conductivity of the drilling mud [8]. In addition, a research performed by Mahmoud, Omar, et al (2017)showed that ferric oxide nanoparticles improved filtration and filter cake properties and make the mud cake less porous [9]. In 2016, Needaa, AL-Malki et al found that the sepiolite nano sized particles would reduce the filtration volume and minimize the mud cake thickness under HPHT conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent these challenges, academics and petroleum practitioners have attempted to develop different additives, including microparticles, synthetic polymers, and their hybrid nanocomposites. [13][14][15] Among these additives, synthetic polymers have gained more attention owing to their targeted properties via chemical modication of functional groups, as well as the regulatable molecular weight. 16 Recently, a large variety of synthetic polymers have been successfully applied in drilling uid systems such as acrylamide-based polymers, [17][18][19] polyacrylates, polyvinyl alcohol 20,21 and functionalized cellulose nanoparticles.…”
Section: Introductionmentioning
confidence: 99%